Hemoconcentration of Creatinine Minimally Contributes to Changes in Creatinine during the Treatment of Decompensated Heart Failure. Issue 6 (30th June 2022) - Maulion, Christopher; Chen, Sheldon; Rao, Veena S.; Ivey-Miranda, Juan B.; Cox, Zachary L.; Mahoney, Devin; Coca, Steven G.; Negoianu, Dan; Asher, Jennifer L.; Turner, Jeffrey M.; Inker, Lesley A.; Wilson, F. Perry; et al.
Key Points: Hemoconcentration is a minimal contributor to changes in serum creatinine during treatment of decompensated heart failure. Changes in GFR is the primary driver of serum creatinine in treatment of decompensated heart failure. Visual Abstract: Abstract : Background: Worsening serum creatinine is common during treatment of acute decompensated heart failure (ADHF). A possible contributor to creatinine increase is diuresis-induced changes in volume of distribution (VD) of creatinine as total body water (TBW) contracts around a fixed mass of creatinine. Our objective was to better understand the filtration and nonfiltration factors driving change in creatinine during ADHF. Methods: Participants in the ROSE-AHF trial with baseline to 72-hour serum creatinine; net fluid output; and urinary KIM-1, NGAL, and NAG were included ( n =270). Changes in VD were calculated by accounting for measured input and outputs from weight-based calculated TBW. Changes in observed creatinine (Crobserved ) were compared with predicted changes in creatinine after accounting for alterations in VD and non–steady state conditions using a kinetic GFR equation (Cr72HR Kinetic ). Results: When considering only change in VD, the median diuresis to elicit a ≥0.3 mg/dl rise in creatinine was −7526 ml (IQR, −5932 to −9149). After accounting for stable creatinine filtration during diuresis, a change in VD alone was insufficient to elicit a ≥0.3 mg/dl rise in creatinine. Larger estimated decreases in VD were paradoxically associated with improvement in Crobserved ( r =−0.18, P =0.003). Overall, −3% of the change in eCr72HR Kinetic was attributable to the change in VD. A ≥0.3 mg/dl rise in eCr72HR Kinetic was not associated with worsening of KIM-1, NGAL, NAG, or postdischarge survival ( P >0.05 for all). Conclusions: During ADHF therapy, increases in serum creatinine are driven predominantly by changes in filtration, with minimal contribution from change in VD.